Laboratory statistics methods in chemistry and health sciences - Kallner, Anders (Amsterdam, Netherlands Elsevier, 2018)
"Presents strategies for comparing and evaluating numerical laboratory data. The text deals with the data and problems that laboratory scientists and students in analytical chemistry, clinical chemistry, epidemiology, and clinical research face on a daily basis. The book takes the mystery out of statistics and provides simple, hands-on instructions in the format of everyday formulas, spreadsheet shortcuts and functions, and many simple worked examples. This thoroughly revised second edition includes several new sections, more examples, and all formulas in Excel code."
Basics -- Distributions of data -- Permutations, combinations, probability, binominal and poisson distributions -- Robust estimators -- Uncertainty -- Difference between results -- Nonparametric comparisons -- Analysis of variance -- Analysis of variance components -- Regression -- Correlation and covariance -- Comparing quantities -- Performance characteristics -- Interpretation of the elements of the ROC analysis -- Other applications -- Estimation of minimal sample size (power analysis) -- Agreement of categorical assessments (kappa (k) statistics) -- Some metrological concepts.
First edition published under title Laboratory statistics: handbook of formulas and terms.
Includes bibliographical references (pages 153-154) and index.
Keywords: Mathematical notation; Mathematics -- Terminology; Dictionaries